A ring D chromosome in association with Down's syndrome-like phenotype - A. Wajntal; A. J. Diament; P. H. Saldanha (Arquivos de Neuro-Psiquiatria, 1973)
The case of a ten-years-old mentally retarded girl with Down's syndrome-like features whose chromosome analysis revealed an unusual mosaicism including 10% mitosis with a ring chromosome replacing a D chromosome is reported. The clinical features of the patient were considered similar to those described by Jacobsen (1966) and Emberger et al. (1971) who interpreted the ring chromosome present in their patients as being chromosome 15. Relata-se um caso de uma menina com 10 anos de idade, mentalmente retardada e com semelhanças com a síndrome de Down, cuja análise cromossômica revelou um mosaicismo pouco freqüente, incluindo 10% de mitoses com um cromossoma em anel substituindo um cromossoma D. O quadro clínico da paciente é similar ao descrito por Jacobsen (1966) e Emberger et al. (1971) que interpretaram a presença do cromossoma em anel em seus pacientes como sendo o cromossoma 15.